Communication Component of the US's Climate Policy - Шевченко, Олена Володимирівна (Київський національний університет імені Тараса Шевченка, 2024)
The article is devoted to the study of the communication component of the US climate policy. In particular, the state of American public opinion regarding global climate change is characterized, approaches to public segmentation for climate communications are determined, communicative challenges to American climate communications are shown, effective communicative messages are analyzed, and the role of the media in conveying climate messages to specific target audiences is determined. It is shown that the segmentation of target audiences for the implementation of climate communications is carried out on the basis of beliefs about climate change, attitudes, risk perception, motivation, values, political preferences and behavior. It was determined that for the formation of public opinion about the causes and consequences of global climate change among the American public, the media is one of the most important channels for the dissemination of climate information.

Стаття присвячена дослідженню комунікаційної складової кліматичної політики США. Зокрема, охарактеризовано стан американської громадської думки щодо глобальних змін клімату, визначено підходи до сегментації громадськості для здійснення кліматичних комунікацій, показані комунікативні виклики американських кліматичним комунікаціям, проаналізовано ефективні комунікативні месаджі,  а також визначено роль медіа у донесенні кліматичних месаджів визначеним цільовим аудиторіям. Показано, що сегментація цільових аудиторій для здійснення кліматичних комунікацій здійснюється на основі переконань про зміни клімату, ставлення, сприйняття ризику, мотивації, цінностей, політичних уподобань та поведінки. Визначено, що для формування громадської думки щодо причин і наслідків глобальних змін клімату серед американської громадськості медіа є одним з найважливіших каналів поширення кліматичної інформації.
Комунікаційна складова кліматичної політики США
Keywords: globalclimatechange; climatecommunications; climatepolicy; USA; глобальнізміни клімату; кліматичні комунікації; кліматична політика; США